Diversity matters: the influence of gender diversity on~the environmental orientation of entrepreneurial ventures - Isabell Tenner; Jacob Hörisch (Journal of Business Economics, 2021)
Environmental entrepreneurship bears great potential to promote sustainable development. Several influencing factors on the level of environmental orientation have been identified by past literature. In this respect, mixed results occur with regard to the influence of gender on environmental entrepreneurship. However, these studies simply investigated the level of a single entrepreneur by distinguishing between male and female individuals, although ventures are increasingly founded by entrepreneurial teams. Consequently, this study quantitatively addresses the research question how the gender of founding teams influences the~environmental orientation of entrepreneurial ventures. Based on a dataset of entrepreneurial ventures from the US and Germany, our results indicate that the level of environmental orientation is not dependent on the share of female members, but rather on the gender diversity of the founding team. We conclude that gender diversity within the entrepreneurial team is necessary to address both ecological and economic goals of environmental entrepreneurship. Based on this finding, theoretical and practical implications are drawn, in particular for policy, entrepreneurial teams and entrepreneurship training.
Keywords: M13; M21; Q01; Q56; 650; Gender; Diversity; Environmental entrepreneurship; Founder; Sustainable development